LITERATURE RIVIEW: PENGARUH PENGGUNAAN ALAT PELINDUNG DIRI (APD) TERHADAP KEJADIAN KERACUNAN PESTISIDA PADA PETANI - Cindy Puspita Ningrum; Susilawati (CV. ADIBA AISHA AMIRA, 2022)
Inappropriate use of chemicals such as pesticides is still a major public health problem in many developing countries. Some examples of cases of unsafe use of pesticides in developing countries, such as the use of chemical pesticides which are prohibited by the Government, excessive spraying of pesticides, lack of awareness in using personal protection, incorrect storage of pesticides, improper handling of pesticide containers and, in cases the extreme, is the reuse of pesticide containers as places for food or drink as reported by 35.4% and 77.2% of farmers in Nigeria and Ethiopia. One of the efforts to prevent pesticide poisoning in farmers is to use complete Personal Protective Equipment (PPE) (Usman, 2011), such as masks, work clothes, boots, and gloves. This study is a literature review with the result that behavior is the main factor in relation to adherence to the use of Personal Protective Equipment (PPE) on farmers. The author uses the literature review method, research articles found in the Google Scholar database. By using the keywords Personal protective equipment (PPE), chemical poisoning, use of pesticides. The purpose of writing this article is to examine more deeply the importance of using PPE when working to prevent poisoning when using pesticides